2013
DOI: 10.1155/2013/574283
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Fatty Acid and Amino Acid Compositions in Okra (Abelmoschus esculentus) Grown in Different Geographical Locations

Abstract: Okra has different uses as a food and a remedy in traditional medicine. Since it produces many seeds, distribution of the plant is also quite easy. Although seed oil yield is low (4.7%), since the linoleic acid composition of the seed oil is quiet high (67.5%), it can still be used as a source of (UNSAT) unsaturated fatty acids. In this study, samples of okra grown in four different locations were analyzed to measure fatty acid and amino acid compositions. The content of the lipid extraction ranged from 4.34% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 13 publications
(13 reference statements)
2
16
0
Order By: Relevance
“…In any case, PUFA/SFA and n-6/n-3 ratios were higher than 0.45 and lower than 4.0, respectively, which both indicate high nutritional value of pods (Guil, Torija, Giménez, & Rodriguez, 1996). Similar results have been reported by Sami, Lianzhou, Yang, Ma, and Jing (2013) who also identified linoleic, palmitic and alpha-linolenic acid as the main fatty acids in sun-dried okra pods collected from different locations in Egypt, in amounts that differed significantly between the tested genotypes. However, fatty acids composition differed significantly from the present study, indicating that apart from genotype growing conditions may also have an impact on chemical composition of okra fruit.…”
Section: Resultssupporting
confidence: 86%
“…In any case, PUFA/SFA and n-6/n-3 ratios were higher than 0.45 and lower than 4.0, respectively, which both indicate high nutritional value of pods (Guil, Torija, Giménez, & Rodriguez, 1996). Similar results have been reported by Sami, Lianzhou, Yang, Ma, and Jing (2013) who also identified linoleic, palmitic and alpha-linolenic acid as the main fatty acids in sun-dried okra pods collected from different locations in Egypt, in amounts that differed significantly between the tested genotypes. However, fatty acids composition differed significantly from the present study, indicating that apart from genotype growing conditions may also have an impact on chemical composition of okra fruit.…”
Section: Resultssupporting
confidence: 86%
“…In addition, during defatting, phenolic fatty acids like those rich in linoleic acid are lost. Oil obtained from okra seeds consist mainly of linoleic acid [12,13,23]. This explains the loss in the total phenol content of the defatted samples since some of the fatty acids removed during defatting contained some phenols.…”
Section: Total Phenol Contentmentioning
confidence: 99%
“…We presented 3 cases of Okra pod FB impaction. It was suggested that Okra seeds can be subjected to oil extraction for additional benefits [5]. To the best of our knowledge, similar cases have never been reported.…”
Section: Discussionmentioning
confidence: 83%